Dampak Lingkungan Pondok Pesantren Terhadap Perkembangan Spiritual Santri di Pondok Pesantren Roudlotut Tholibin, Kepil, Wonosobo - Ahmad Munir; Asep Sunarko; Nasokah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This thesis aims to examine the spiritual conditions surrounding the Islamic boarding school, identify the spiritual atmosphere within the boarding school environment, and analyze the supporting and inhibiting factors influencing the spiritual development of students at the Roudlotut Tholibin Islamic Boarding School in Kepil District, Wonosobo Regency. This research uses a descriptive qualitative field method with data collected through observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and conclusion drawing. The findings indicate that the spiritual condition of the community around the boarding school shows significant positive development. The community experiences an improvement in religious quality through interactions with students and participation in boarding school activities. Within the boarding school, students’ spirituality is strengthened through routine worship, discipline, and habituation of Islamic etiquette. Supporting factors include a strong religious culture, disciplined worship practices, exemplary behavior of the ustadz, and community support. Meanwhile, minor inhibiting factors arise from students’ varied backgrounds, early adaptation challenges, and emotional conditions requiring further guidance.